EMPOWERMENT OF VILLAGE OFFICIALS IN REALIZING A DIGITAL VILLAGE THROUGH ASSISTANCE WITH A GIS-BASED DIGITAL VILLAGE INFORMATION SYSTEM IN BUDDAGAN VILLAGE, PAMEKASAN REGENCY - Darmawan, Aang; Daryanto, Eko; Muqaddas, Zaiful; Kartini, Kartini; Anekawati, Anik; Umam, Busro Akramul; Muhsi, Muhsi (International Journal of Engagement and Empowerment (IJE2), 2024)
Villages face challenges in the digital age due to weak governance, poor data quality, and conventional record-keeping methods. Initiatives like digital villages, integrated criminal justice systems, and online platforms address these issues. Digital GIS mapping enhances precision agriculture, sustainable food production, and decision-making by assessing soil quality, infrastructure, and weather. It also aids in land management and remote sensing data. However, Digital villages in Indonesia face challenges due to poor data quality, lack of knowledge, and inadequate technology integration, hindering community services and maximizing potential. Buddagan Village, situated in Pademawu sub-district, East Java, faces challenges such as weak management of village archives, lack of a village potential map, and inadequate digital-based archives, which could hinder community access and decision-making. This community service activity aims to (1)build a GIS-based Digital Village Information System (SIDD) in Buddagan Village, (2)create a digital map of village potential, (3)train village officials, and (4)conduct workshops and FGDs to improve governance, public services, and community welfare. The output of this activity produces (1) a Web-based digital village information system (SIDD), (2) a Buddagan Village official website, (3) a digital map of agricultural potential, and (4) a Monograph book: GIS-based digital village information system.  The study evaluated Buddagan Village's community service activities, revealing significant improvements in officials' understanding and skills. Post-training, officials' skills increased from 20% to 80%, and community participation in managing potential increased from 40% to 70%. Transparency and accountability increased with an official website and adequate information system